The Relative Importance of Female Education on Fertility Desires in Sub-Saharan Africa: A Multi-Level Analysis - Endale Birhanu Kebede (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
Scholars suggest that in high fertility settings where there is high wanted fertility, lowering the desired family size is a necessary precondition for fertility declines. Though accumulated evidence has linked socio-economic developments to changes in fertility desires, little efforts have taken to disentangle the relative importance of key socio-economic determinants such as education, income, and area of residence in a multi-level context. Combining individual and community-level data from Demographic and Health Surveys of 34 African countries to aggregate level indicators, we have quantified and compared the relative role of female education on fertility desire at the individual, community, and country levels. Results show that at the individual level, female education has a stronger effect compared to household wealth, and area of residence. The high levels of reported desired family size in the rural parts of SSA are mainly a consequence of their relatively lower levels of educational attainment compared to their urban counterparts. At the community level, the relative impact of female education is even more striking. The simulation results revealed that moving the most economically disadvantaged and illiterate woman from a low educated to a high-educated community would reduce her desired family size by about 20 percent. On the other hand, lifting the same woman from the poorest to the wealthiest community would reduce her family size desire only by 6 percent. Our findings are robust to alternative measures of fertility preferences. This study, thus, confirmed the findings of previous studies that have looked at the relationship and causal link between actual fertility and women's level of educational attainment.
Keywords: 300; Desired fertility; sub-Saharan Africa; female education; multi-level analysis; community education